A importância das redes de relacionamento para se formar uma parceria : um estudo de caso na ALESAT - Cunha, Eliza Catarina Bezerra (2008)
This paper consists in a study case at the Alesat company, which aims at analyzing how the networks from the former companies Ale and Sat influence the formation of partnerships. The study was based on literature by Burt (1992), Granovetter (1973), Uzzi (1997), Contractor and Lorange (1988), Gulati (1998), Child and Faulkner (1998), and others, to verify how important the social relations were between the companies to the formation of a strategic alliance. The research method we adopted analyzed the first partnership between Ale and Sat and the last one that ended up with the merger of the companies resulting in a new company, Alesat. Semi-structured interviews were conducted in 2008 with the council board of the company. Secondary data were also collected from specific web sites from the area, such as ANP, Sindicom and Fecombustíveis, as well as from important newspapers in the market. The primary data were analyzed through the content analysis technique from Triviños (1987). The secondary data were analyzed through the documental analysis technique from Richardson (1985). This way, through the data collected, it can be concluded that the social ties between the companies were important in the partnership, and among the reasons that made the companies get together, the key one was the fact that the union would make possible to the companies act in regions in which they didn t have too much market share, making them a bigger player nationally wise